Self-Damage Caused by Dysregulation of the Complement Alternative Pathway: Relevance of the Factor H Protein Family - Sánchez-Corral, Pilar; Pouw, Richard B.; López-Trascasa, Margarita; Józsi, Mihály (Frontiers in Immunology, 2018)
The alternative pathway is a continuously active surveillance arm of the complement system, and it can also enhance complement activation initiated by the classical and the lectin pathways. Various membrane-bound and plasma regulatory proteins control the activation of the potentially deleterious complement system. Among the regulators, the plasma glycoprotein factor H is the main inhibitor of the alternative pathway and its powerful amplification loop. Factor H belongs to a protein family that also includes factor H-like protein 1 and five factor H-related proteins (FHR-1 to FHR-5). Genetic variants and abnormal rearrangements involving the factor H protein family have been linked to numerous systemic and organ-specific diseases, including age-related macular degeneration, and the renal pathologies atypical hemolytic uremic syndrome, C3 glomerulopathies and IgA nephropathy. This review covers the known and recently emerged ligands and interactions of the human factor H family proteins associated with disease and discuss the very recent experimental data that suggest factor H-antagonistic and complement activating functions for the FHR proteins.